Immune profiling of influenza‐specific B‐ and T‐cell responses in macaques using flow cytometry‐based assays. Issue 1 (7th September 2020) - Koutsakos, Marios; Sekiya, Toshiki; Chua, Brendon Y; Nguyen, Thi Hoang Oanh; Wheatley, Adam K; Juno, Jennifer A; Ohno, Marumi; Nomura, Naoki; Ohara, Yuki; Nishimura, Tomohiro; Endo, Masafumi; Suzuki, Saori; et al.
Abstract: Influenza remains a significant global public health burden, despite substantial annual vaccination efforts against circulating virus strains. As a result, novel vaccine approaches are needed to generate long‐lasting and universal broadly cross‐reactive immunity against distinct influenza virus strains and subtypes. Several new vaccine candidates are currently under development and/or in clinical trials. The successful development of new vaccines requires testing in animal models, other than mice, which capture the complexity of the human immune system. Importantly, following vaccination or challenge, the assessment of adaptive immunity at the antigen‐specific level is particularly informative. In this study, using peripheral blood mononuclear cells (PBMCs) from cynomolgus macaques, we describe detection methods and in‐depth analyses of influenza virus‐specific B cells by recombinant hemagglutinin probes and flow cytometry, as well as the detection of influenza virus‐specific CD8 + and CD4 + T cells by stimulation with live influenza A virus and intracellular cytokine staining. We highlight the potential of these assays to be used with PBMCs from other macaque species, including rhesus macaques, pigtail macaques and African green monkeys. We also demonstrate the use of a human cytometric bead array kit in detecting inflammatory cytokines and chemokines from cynomolgus macaques to assess cytokine/chemokine milieu. Overall, the detection of influenza virus‐specific B and T cells, together with inflammatory responses, as described in our study, provides useful insights for evaluating novel influenza vaccines. Our data deciphering immune responses toward influenza viruses can be also adapted to understanding immunity to other infections or vaccination approaches in macaque models. Abstract : Nonhuman primates (NHPs) are an integral part of translational immunology and the development of effective vaccines and therapeutics. However, the analysis of antigen‐specific B and T cells is often overlooked. This work describes and validates two assays for the quantitative and qualitative analyses of influenza virus‐specific B and T cells in cynomolgus macaques as well as their applicability in other macaque species. It further demonstrates the use of a human cytometric bead array kit in detecting inflammatory cytokines and chemokines from cynomolgus macaques to assess cytokine/chemokine milieu. Collectively, our study defines novel and broadly applicable assays for the antigen‐specific analysis of B and T cells in NHPs that could aid the development and translation of effective vaccines and therapeutics.